2003
DOI: 10.1093/jxb/erg183
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally-induced changes in protein composition in developing grains of wheat are related to changes in total protein content

Abstract: Nitrogen (N) nutrition, post-anthesis temperature and drought-induced changes in the kinetics of accumulation of dry mass, total grain N and protein fractions (albumins-globulins, amphiphils, gliadins, and glutenins) contents were examined for winter wheat (Triticum aestivum L.). Crops were grown in controlled environment tunnels in 1994 and 1998. In 1994, five post-anthesis temperatures averaging from 15-25 degrees C were applied during grain-filling. In 1998 two post-anthesis temperatures averaging 13 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
194
3
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(238 citation statements)
references
References 53 publications
20
194
3
11
Order By: Relevance
“…However, the enhanced β-amylase activity under high temperature was associated with the decrease of grain weight and it may be assumed that the increase in β-amylase activity will not improve malting quality, as protein content is also increased simultaneously and starch accumulation is reduced in mature grains. In wheat, it was found that structural/ metabolic protein fractions accumulate mainly during the early phase of grain growth, when most endosperm cells are still dividing, whereas the accumulation of storage protein fractions appears later in grain development, when cell division has stopped 30 . In the current study, it was found that albumins were the least affected and glutelins was the most affected protein fraction when the plants were exposed to high temperature during grain development, suggesting that albumins are mainly synthesized in the early period of the grain filling stage and glutelins, mainly a storage protein, occur later.…”
Section: Discussionmentioning
confidence: 99%
“…However, the enhanced β-amylase activity under high temperature was associated with the decrease of grain weight and it may be assumed that the increase in β-amylase activity will not improve malting quality, as protein content is also increased simultaneously and starch accumulation is reduced in mature grains. In wheat, it was found that structural/ metabolic protein fractions accumulate mainly during the early phase of grain growth, when most endosperm cells are still dividing, whereas the accumulation of storage protein fractions appears later in grain development, when cell division has stopped 30 . In the current study, it was found that albumins were the least affected and glutelins was the most affected protein fraction when the plants were exposed to high temperature during grain development, suggesting that albumins are mainly synthesized in the early period of the grain filling stage and glutelins, mainly a storage protein, occur later.…”
Section: Discussionmentioning
confidence: 99%
“…Although albumins-globulins have only a slight influence on the dough quality, they are important from the nutritional point of view, due to their high contents of essential amino acids. Gupta et al (1992) and Triboï et al (2003) reported an increase in the gliadin proportion and a reduction in the glutenin proportion as the protein content of the flour increased. The ratio of albumins-globulins did not increase proportionately with the protein content in response to a rise in temperature (Gupta et al 1992;Wieser & Seilemeier 1998;Triboï et al 2003).…”
mentioning
confidence: 98%
“…Gupta et al (1992) and Triboï et al (2003) reported an increase in the gliadin proportion and a reduction in the glutenin proportion as the protein content of the flour increased. The ratio of albumins-globulins did not increase proportionately with the protein content in response to a rise in temperature (Gupta et al 1992;Wieser & Seilemeier 1998;Triboï et al 2003). It was demonstrated by Zhao et al (2009) that protein components are very sensitive to drought stress during the later phenophases of grain-filling.…”
mentioning
confidence: 98%
“…No entanto, a constituição genética da cultivar e sua interação com o ambiente em que foi originada, podem afetar o percentual de germinação das sementes (DODD & DONOVAN 1999), principalmente devido as mudanças na organização estrutural e síntese proteica no momento da germinação do embrião (RAMAGOPAL 1990). Em nível fisiológico, a formação de proteínas, importantes no processo de germinação das sementes, envolve mecanismos de absorção de nitrogênio pelas raízes, acúmulo nos órgãos vegetativos e posterior remobilização para os grãos para a formação e configuração proteica (TRIBOÏ et al 2003). Este nitrogênio remobilizado é responsável por cerca de 80% do conteúdo total do nutriente no grão (SUPRAYOGI et al 2011 e aproveitamento deste nutriente.…”
Section: Averages For Interaction Between Cultivars (Tbio Mestre Tbiunclassified